Root and canal morphology of mandibular second molars in a Chinese Kazakh population by cone-beam computed tomography - Shuchun Yang; Chenye Li; Hui Shi; Ming Liu; Xu Wang (BMC Oral Health)
Abstract Objective This study aimed to investigate variations in root and canal morphology of the mandibular second molars in a Chinese Kazakh population using cone-beam computed tomography (CBCT). Methods A total of 374 mandibular second molars from 236 patients were included in the retrospective study. The mandibular second molars were categorized based on the radiographic morphology of their external roots: non-fused roots (NFR), fused roots (FR), and single roots with a single canal (SS). The configuration of the C-shaped canal at three different levels was categorized into C1-C5. A chi-square test was employed to assess the association between the incidence of C-shaped root canals and demographic factors such as sex and tooth position. Results Mandibular second molars typically had two roots. C-shaped root canals appeared in 33.1% of second molars. The C-shaped form was most prominent in C3, followed by C1. Sex and tooth position did not exhibit notable differences. Conclusions The incidence of C-shaped root canals in the Chinese Kazakh population was similar to that previously reported in Asian populations and higher than in Caucasian and Middle Eastern populations.